2004
DOI: 10.1177/0146167204264080
|View full text |Cite
|
Sign up to set email alerts
|

Social Identity and Worldview Validation: The Effects of Ingroup Identity Primes and Mortality Salience on Value Endorsement

Abstract: In this article, the authors report an investigation of the relationship between terror management and social identity processes by testing for the effects of social identity salience on worldview validation. Two studies, with distinct populations, were conducted to test the hypothesis that mortality salience would lead to worldview validation of values related to a salient social identity. In Study 1, reasonable support for this hypothesis was found with bicultural Aboriginal Australian participants (N = 97).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 49 publications
7
57
0
2
Order By: Relevance
“…Situations that make an outgroup salient or contain threats to one's identity also heighten adherence to ingroup norms (Elsbach, 2003;Petriglieri, 2011). Halloran and Kashima (2004) found that bicultural Australian aboriginals were more affected by group primes when under the condition of mortality anxiety, consistent with the hypothesis that group identifications buffer people against existential threats. Individuals also engage in prototypical behavior to earn standing within the group, which entitles them to leadership or idiosyncrasy (van Knippenberg & Hogg, 2003).…”
Section: Social Identitysupporting
confidence: 64%
“…Situations that make an outgroup salient or contain threats to one's identity also heighten adherence to ingroup norms (Elsbach, 2003;Petriglieri, 2011). Halloran and Kashima (2004) found that bicultural Australian aboriginals were more affected by group primes when under the condition of mortality anxiety, consistent with the hypothesis that group identifications buffer people against existential threats. Individuals also engage in prototypical behavior to earn standing within the group, which entitles them to leadership or idiosyncrasy (van Knippenberg & Hogg, 2003).…”
Section: Social Identitysupporting
confidence: 64%
“…Similarly, the epistemic motive of need for closure leads to heightened conformity to the norms of one's culture in attributional judgments (Chiu, Morris, Hong, & Menon, 2000) and conflict resolution decisions (Fu et al, 2007). Biculturals with high levels of these existential and epistemic motives tend to conform to whichever of their two cultures has been made most salient by the situation (Halloran & Kashima, 2004;Kosic, Kruglanski, Pierro, & Mannetti, 2004).…”
Section: Cultural Identificationmentioning
confidence: 99%
“…Value expression is assumed to be tied to specific situations and contexts (Seligman & Katz, 1996). Research by Halloran and Kashima (2004) has shown, for instance, that Australian students supported egalitarianism more so when their Australian identity rather than when either their student or personal identity was made salient. Thus, participants in Study 1 were asked to complete a measure of a range of value types and a measure of reconciliation attitudes under two instructional sets: either as an Australian or an individual.…”
Section: Studymentioning
confidence: 99%